Adaptability and stability of the zinc density in cowpea genotypes through GGE-Biplot method - Oliveira, Diêgo Sávio (2017)
Biofortification is a strategy that aims to improve the nutritional quality of foods through genetic breeding. Zinc is an important mineral for human health. It is used in various physiological processes such as immune function, antioxidant protection, growth and development. Therefore, zinc is one of the most studied minerals in the biofortification of grains in cowpea. The objective of this study was to evaluate the adaptability and stability of zinc density in the grain of 12 cowpea genotypes in four environments in the states of Piauí (PI) and Maranhão (MA), Brazil, by using the GGE-Biplot method. A randomized complete block design with four replications was used. Grain samples of each genotype were ground and the resulting flour was subjected to zinc density analysis by using an atomic flame absorption spectrophotometer. Analyses of variance were performed, and the adaptability and stability of zinc density in the grain was evaluated by the GGE-Biplot method. Genotypes showed different behavior depending on the environments tested for zinc concentration. According the GGE-Biplot method, Parnaiba-PI was the most discriminating environment for genotypes. Campo Grande do Piauí-PI and Parnaíba-PI were the most representative environments for selecting genotypes with zinc biofortification in the state of Piauí. Parnaíba-PI was the optimal environment for selection of genotypes adapted to high zinc density in grain. The cultivar BRS Xiquexique was the ideal genotype due to the high zinc density in the grain and high stability according to GGE-Biplot, followed by the lines MNC04-774F-78 and MNC04-782F-108.